Morphological knowledge affects processing of L2 derivational morphology: An event-related potential study. (February 2016) - Deng, Taiping; Shi, Jiawei; Dunlap, Susan; Bi, Hongyan; Chen, Baoguo
Abstract: This study used event-related potentials (ERPs) to investigate the effect of morphological knowledge on L2 derivational processing in a sentence reading task with Chinese-English bilinguals. Correctly derived words and pseudo-derived words were embedded in a semantically plausible sentence. Compared with the correctly derived words, a significant P600 to pseudo-derived words was elicited in the group with high morphological knowledge, indicating their sensitivity to rule violations and application of rule-based decomposition. For the group with low morphological knowledge, a significant N400 was observed, suggesting that participants in this group depend more on a whole-word processing mechanism. These results suggest that morphological knowledge plays an important role in L2 processing of derivational morphology. Highlights: Learner with low L2 morphological knowledge showed a N400 to pseudo-derived words. Learner with high L2 morphological knowledge showed a P600 to pseudo-derived words. Morphological knowledge plays an important role in L2 derivational processing.